Nijmegen breakage syndrome: case report and review of literature - Hasbaoui, Brahim El (Pan Afr Med J, 2020)
Nijmegen Breakage Syndrome (NBS) is a rare autosomalrecessive DNA repair disorder characterized by genomic instability andincreased risk of haematopoietic malignancies observed in morethan 40% of the patients by the time they are 20 years old. The underlying gene, NBS1, is located on human chromosome 8q21 and codes for a protein product termed nibrin, Nbs1 or p95. Over 90% of patients are homozygous for a founder mutation: a deletion of five base pairs which leads to a frame shift and protein truncation. Nibrin (NBN) plays an important role in the DNA damage response (DDR) and DNA repair. DDR is a crucial signalling pathway in apoptosis and senescence. Cardinal symptoms of Nijmegen breakage syndrome are characteristic: microcephaly, present at birth and progressive with age, dysmorphic facial features, mild growth retardation, mild-to-moderate intellectual disability, and, in females, hypergonadotropic hypogonadism. Combined cellular and humoral immunodeficiency with recurrent sino-pulmonary infections, a strong predisposition to develop malignancies (predominantly of lymphoid origin) and radiosensitivity are other integral manifestations of the syndrome. The diagnosis of NBS is initially based on clinical manifestations and is confirmed by genetic analysis. Prenatal molecular genetic diagnosis is possible if disease-causing mutations in both alleles of the NBN gene are known. No specific therapy is available for NBS; however, hematopoietic stem cell transplantation may be one option for some patients. Prognosis is generally poor due to the extremely high rate of malignancies. We present here a case of Nijmegen breakage syndrome associated with Hodgkin lymphomas and Combined variable immunodeficiency.